The COVID-19 nutrition crisis: What to expect and how to protect - Headey, Derek D.; Ruel, Marie T. (International Food Policy Research Institute, 2020)
The COVID-19 pandemic has all the makings of a perfect storm for global malnutrition. The crisis will damage the nutritional status of vulnerable groups through multiple mechanisms. We can expect a dangerous decline in dietary quality in low- and middle-income countries (LMICs) stemming from the income losses related to government-mandated shutdowns and de-globalization, as well as from the freezing of food transfer schemes such as school feeding programs and the breakdown of food markets due to both demand shocks and supply constraints. But malnutrition will also increase due to healthcare failures, as already strained healthcare systems are forced to divert resources from a range of nutritionally important functions — including antenatal care, immunization, micronutrient supplementation, and prevention and treatment of childhood diarrhea, infections, and acute malnutrition — toward combating COVID-19.